Electrophoretic behavior of DNA‐methyl‐CpG‐binding domain protein complexes revealed by capillary electrophoreses laser‐induced fluorescence. Issue 24 (21st October 2015) - Zhong, Shangwei; Zou, Dandan; Zhao, Bailin; Zhang, Dapeng; Li, Xiangjun; Wang, Hailin
Abstract : The free solution electrophoretic behavior of DNA‐protein complexes depends on their charge and mass in a certain experimental condition, which are two fundamental properties of DNA‐protein complexes in free solution. Here, we used CE LIF to study the free solution behavior of DNA‐methyl‐CpG‐binding domain protein (MBD2b) complexes through exploring the relationship between the mobilities, charge, and mass of DNA‐protein complexes. This method is based on the effective separation of free DNA and DNA‐protein complexes because of their different electrophoretic mobility in a certain electric field. In order to avoid protein adsorption, a polyacrylamide‐coated capillary was used. Based on the evaluation of the electrophoretic behavior of formed DNA‐MBD2b complexes, we found that the values of (μ0 /μ)‐1 were directly proportional to the charge‐to‐mass ratios of formed complexes, where the μ0 and μ are the mobility of free DNA probe and DNA‐protein complex, respectively. The models were further validated by the complex mobilities of protein with various lengths of DNA probes. The deviation of experimental and calculated charge‐to‐mass ratios of formed complexes from the theoretical data was less than 10%, suggesting that our models are useful to analyze the DNA‐binding properties of the purified MBD2b protein and help to analyze other DNA‐protein complexes. Additionally, this study enhances the understanding of the influence of the charge‐to‐mass ratios of formed DNA‐protein complexes on their separation and electrophoretic behaviors.